The perception and treatment of mental illness by selected Pentecostal pastors in Polokwane : towards an intervention - Mauda, Lesley Takalani (My University, 2022)
Mental illness is a high burden of disease especially in Low- and Medium-Income Countries (LMICs) like South Africa. In many LMICs, there is a paucity of Mental Health Professionals (MHCPs). As a result, people with mental illness call their faith healers or religious/spiritual leaders (pastors in this study) when experiencing mental health problems. Pastors are more accessible, share the same religious/spiritual beliefs about mental illness with their congregants and often provide religious/spiritual solutions to those who consult with them. Thus, they are often preferred over MHCPs. However, pastors are rarely involved as partners in community based mental health programs. While mental illness is mainly clinically diagnosed and recognised by MHCPs using the DSM-5 and ICD-10 codes, less is known in South Africa with regards to the views of pastors with regards to their notions of what mental illness is. Thus, it may be complex for Pentecostal pastors to clearly distinguish between spirit possession and mental illness as much as it is complex for MHCPs who struggle with accommodating their patients’ religious/spiritual beliefs. Religious/spiritual beliefs are significant in many Africans seeking mental health recovery. However, less has been explored in South Africa in the area of religion/spirituality and its relevance in the practice of clinical psychology. Western based psychotherapeutic methods of intervention which exclude the religious/spiritual domain of African clients continue to dominate the practise of psychology in Africa. Given the above, this study aimed to explore and understand selected Pentecostal pastors’ perception and treatment of mental illness. The research objectives were, namely: (1) to establish the notions held by Pentecostal pastors’ regarding what mental illness is (2) to establish Pentecostal pastors’ perception of what causes mental illness; (3) to determine Pentecostal pastors’ perceptions of how and by whom mental illness can be recognised, diagnosed, treated and managed; (4) To determine Pentecostal pastors’ views regarding their own roles in the management of mental illness; and (5) To canvass and describe Pentecostal pastors’ perceptions about collaboration for purposes of an intervention programme aimed at providing a holistic care and treatment of religious/spiritual patients. The study was qualitative, and the exploratory research approach was adopted. The research was informed by the Bio-Psycho-Social-Spiritual (BPSS) model. Purposive sampling was used to select nineteen (19) participants. In-depth semi-structured interviews were conducted. Data were analysed using Thematic Analysis (TA). The following six major themes emerged from the analysed data: (i) Notions of mental illness; (ii) Causes of mental illness;(iii) Recognition and diagnosis of mental illness (iv) Notions on the treatment and management of mental illness; (v) Perceived roles in the treatment and management of mental illness; (vi) Views regarding collaboration with MHCPs. The participants held a multifactorial view of mental illness. They were limited in their understanding of mental illness and perceived it mainly to be madness (psychosis). The participants’ perception of mental illness was influenced by their theological (Pentecostal) as well as their cultural backgrounds (Black Africans). The participants indicated that they lacked training in mental health issues. As such, they were not opposed to collaborating with MHCPs. They mentioned that their roles included counselling, prayer, support, and referral. This study also discovered that Pentecostal pastors upheld three treatment approaches of mental illness namely: The Full-Collaborative Approach; The Partial-Collaborative Approach and the Non-Collaborative Approach. Findings of the study were discussed, and recommendations were made including the proposed intervention programme between pastors and MHCPs with the aim of facilitating a referral process and collaboration between the two professions.
Thesis (Ph.D. (Psychology)) -- University of Limpopo, 2022.
Keywords: Pentecostal pastor; Mental illness; Mental health; LMICs; MHCPs; Bio-Psycho-Social-Spiritual; Religion/Spirituality; DSM-5; ICD-10; Treatment; Intervention programme; Mental illness -- Alternative treatment -- South Africa; Spiritual healing -- Pentacostal churches; Mental health -- Religious aspects; Mental illness -- Religious aspects